Mobility Service Applications to Facilitate Better MSME Financial Performance - Jannah, Elok Nur; Zuhroh, Diana; Parawiyati, Parawiyati (University of Merdeka Malang, 2021)
Mobility service applications widely used by MSMEs during the Covid-19 pandemic include those offered by Go-Jek and Grab (Paath. et al. l, 2019). Based on field observations of MSME merchants, there was a rise in the use of Go-food and other applications during the Covid-19 pandemic, owing to social distancing circumstances and limitations on communal activities. The purpose of this research is to determine the impact of education level and the use of Accounting Information Systems (AIS) on the financial performance of Micro, Small, and Medium-Sized Enterprises (MSMEs), as well as the effect of the use of mobility service platforms as a moderating variable. In the study, the Mobility Service Applications that assist MSME business operations are Gojek and Grab. This is a quantitative study using data collected through questionnaires and surveyed 167 MSMEs. Data processing is MRA analysis. According to the findings, as a moderating variable, the mobility service platform substantially impacted financial performance. The study’s findings also indicate that a high level of education and the use of an adequate accounting information system may help MSMEs improve their financial performance. Through information technology systems, mobility service applications, including transportation services, may help MSME traders improve their financial performance by using different applications, operating systems, and networks to share information. The study findings are helpful to the success of the government’s MSME digitalization initiative, particularly the Ministry of Cooperatives and MSMEs.JEL: B21, O12, O14, G21